Treatment of bipolar disorder. - Geddes, J; Miklowitz, D (2013)
We review recent developments in the acute and long-term treatment of bipolar disorder and identify promising future routes to therapeutic innovation. Overall, advances in drug treatment remain quite modest. Antipsychotic drugs are effective in the acute treatment of mania; their efficacy in the treatment of depression is variable with the clearest evidence for quetiapine. Despite their widespread use, considerable uncertainty and controversy remains about the use of antidepressant drugs in the management of depressive episodes. Lithium has the strongest evidence for long-term relapse prevention; the evidence for anticonvulsants such as divalproex and lamotrigine is less robust and there is much uncertainty about the longer term benefits of antipsychotics. Substantial progress has been made in the development and assessment of adjunctive psychosocial interventions. Long-term maintenance and possibly acute stabilisation of depression can be enhanced by the combination of psychosocial treatments with drugs. The development of future treatments should consider both the neurobiological and psychosocial mechanisms underlying the disorder. We should continue to repurpose treatments and to recognise the role of serendipity. We should also investigate optimum combinations of pharmacological and psychotherapeutic treatments at different stages of the illness. Clarification of the mechanisms by which different treatments affect sleep and circadian rhythms and their relation with daily mood fluctuations is likely to help with the treatment selection for individual patients. To be economically viable, existing psychotherapy protocols need to be made briefer and more efficient for improved scalability and sustainability in widespread implementation.